PENGARUH KEPEMILIKAN MANAJERIAL, INSTITUSIONAL DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Sari, Padma Adriana; Handini, Berlia Tri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2021)
This study aims to analyze the influence of managerial ownership, institutional ownership and audit committee on the disclosure of Corporate Social Responsibility. The population in this study is consumer goods industry company registered in the Indonesian Stock Exchange period 2014 to 2018. The research sample was selected using purposive sampling method with a total of 16 companies and a period of 4 years. The research uses quantitative methods with multiple linear regression methods. The results showed that managerial ownership had no significant effect on CSR disclosure, institutional ownership had a significant positive effect on CSR disclosure and audit committees had a significant positive effect on CSR disclosure.